Strontium-doped lanthanum manganite powders used as cathode in solid oxide fuel cells - Chiba, Rubens; Vargas, Reinaldo Azevedo; Andreoli, Marco; Seo, Emilia Satoshi Miyamaru (Revista Ciências Exatas, 2008)
Nowadays, the strontium-doped lanthanum manganite (LSM - La1-XSrXMnO3) is one of the most common cathodic materials used in the solid oxide fuel cells (SOFC). The dopant strontium increases the electronic conductivity of the material, besides presenting an excellent electrochemical performance, relatively good chemical and thermal stability and compatibility with solid electrolyte of yttria stabilized zirconia (YSZ - ZrO2 /Y2O3). In this work, a contribution to the study of synthesis of La1-XSrXMnO3 with 15 and 50 mol % strontium concentrations by the citrate technique is presented. In this synthesis, it was adopted different concentrations of dopant for identification of the best composition of this material as cathode of SOFC. The resins have been characterized by Thermal Gravimetric Analysis (TGA) and Thermal Differential Analysis (TDA); and the powders have been characterized by Gas Absorption (LECO), X Ray Fluorescence Spectroscopy (XRF), Granulometry by Laser Scattering (CILAS), Gas Adsorption (BET),Picnometry by Gas Helium, Scanning Electron Microscopy (SEM), X Ray Diffractometry (XRD) and Dilatometry. The adequate characteristics of La1-XSrXMnO3 have been evaluated aiming at the use in the preparation of cathodic suspensions for fine films of the SOFC.